2017
DOI: 10.1007/s11746-017-2983-1
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Acer truncatum Seed Oil Extracted Using Supercritical Carbon Dioxide

Abstract: Acer truncatum seed oil rich in nervonic acid was extracted using supercritical carbon dioxide. GC (Gas Chromatography) analysis revealed that the oil contained approximately 6.22% nervonic acid. The sn‐2 compositions were also determined using lipase hydrolysis. A total of 52 triacylglycerides (TAG) were tentatively identified in the oil using an ultra‐performance convergence chromatography (UPC2) coupled with quadrupole time‐of‐flight mass spectrometry (Q‐TOF‐MS) for the first time. In addition, the contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Therefore, fatty acid composition and content profiles can be used as fingerprints to identify useful biological resources, in addition to their current use for oil authentication (Li et al, 2011). At the species level, a total of 15 distinct fatty acid components were detected in this study (Table 2), the results are similar to Hu et al (2017), and a number similar to that was obtained for X. sorbifolia by Yu et al (2017), although their oil content differed from values reported here. Unsaturated fatty acids mainly include oleic acid (C18:1) (25.19%), linoleic acid (C18:2) (32.97%), linolenic acid (C18:3) (2.76%), cis-11-eicosenoic acid (C20:1) (7.90%), erucic acid (C22:1) (16.49%), nervonic acid (C24:1) (5.76%) and small amounts of Palmitoleic acid (C16:1) (0.09%), heptadecenoic acid (C17:1) (0.03%), and cis-11,14-eicosadienoic acid (C20:2) (0.29%).…”
Section: Fatty Acid Compositionsupporting
confidence: 72%
“…Therefore, fatty acid composition and content profiles can be used as fingerprints to identify useful biological resources, in addition to their current use for oil authentication (Li et al, 2011). At the species level, a total of 15 distinct fatty acid components were detected in this study (Table 2), the results are similar to Hu et al (2017), and a number similar to that was obtained for X. sorbifolia by Yu et al (2017), although their oil content differed from values reported here. Unsaturated fatty acids mainly include oleic acid (C18:1) (25.19%), linoleic acid (C18:2) (32.97%), linolenic acid (C18:3) (2.76%), cis-11-eicosenoic acid (C20:1) (7.90%), erucic acid (C22:1) (16.49%), nervonic acid (C24:1) (5.76%) and small amounts of Palmitoleic acid (C16:1) (0.09%), heptadecenoic acid (C17:1) (0.03%), and cis-11,14-eicosadienoic acid (C20:2) (0.29%).…”
Section: Fatty Acid Compositionsupporting
confidence: 72%
“…Nimet et al and Zhao et al evaluated the extraction of sunflower and radish seed oil, respectively, and report that the use of supercritical CO 2 favoured the extraction of tocopherols when compared to propane. Furthermore, some studies have shown that the use of supercritical CO 2 is more advantageous than the use of n ‐hexane for the extraction of tocopherols …”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported that linoleic acid-rich olive oil could induce a higher intracellular TAG accumulation in macrophages compared with oleic acid-rich olive oil (Quintero-Fl orez et al, 2015). In 2017, one study about the nutritional values of Acer truncatum seed oil represented that the sn-position of nervonic acid might be limited due to its sn-position (Hu et al, 2017). And the results in this study also confirmed that sn-1,3 fatty acids could be hydrolysed by pancreatic lipase, thus releasing sn-2 monoacylglycerols that could be absorbed efficiently.…”
Section: Introductionmentioning
confidence: 99%